Revision of the species of the bee genus Caenohalictus (Hymenoptera: Halictidae) occurring in Argentinean Patagonia - Gonzalez-Vaquero, Rocio Ana; Roig-Alsina, Arturo (Zootaxa, 2013)
The species of the halictid bee genus Caenohalictus Cameron occurring in Argentinean Patagonia are revised. Eight spe-cies are recognized, one of them here described as new: Caenohalictus flammeus n. sp. The female of C. turquesa Rojas & Toro 2000 is described for the first time. Pseudagapostemon babuarus Jörgensen 1912, based on the male holotype, is synonymized under Augochlora (Pseudaugochloropsis) thamyris Jörgensen 1912, based on the female lectotype. Lecto-types are designated for Augochlora (Pseudaugochloropsis) thamyris Jörgensen 1912 and Halictomorpha autumnalis Jör-gensen 1912. Caenohalictus cyanopygus Rojas & Toro 2000, C. galletue Rojas & Toro 2000, C. iodurus (Vachal 1903), C. opaciceps (Friese 1916), and C. turquesa Rojas & Toro 2000, all known from Chile, are cited for Argentina for the first time. Notes on the variation observed within species, images of diagnostic structures, a key to the species and distribu-tional data are provided. In addition, DNA barcoding results for four species are briefly discussed.